2014
DOI: 10.1371/journal.ppat.1004555
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Acidocalcisome, an Organelle Conserved from Bacteria to Human Cells

Abstract: Acidocalcisomes are acidic organelles present in a diverse range of organisms from bacteria to human cells. In this study acidocalcisomes were purified from the model organism Trypanosoma brucei, and their protein composition was determined by mass spectrometry. The results, along with those that we previously reported, show that acidocalcisomes are rich in pumps and transporters, involved in phosphate and cation homeostasis, and calcium signaling. We validated the acidocalcisome localization of seven new, put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
120
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 104 publications
6
120
0
Order By: Relevance
“…This perhaps represents a partial compensation, in which energy is stored in phosphoanhydride bonds of inositol pyrophosphates rather than polyP. It is clear that the additional energy stored in the phosphoanhydride bonds of InsP 7 and InsP 8 in ppk1 will not be equal to that accumulated in WT polyP. However, these results do confirm a metabolic interplay between these two families of phosphate-rich molecules and their ability to regulate or be regulated by cellular energy metabolism.…”
Section: Altered Atp and Accumulation Of Inositol Pyrophosphates In Pmentioning
confidence: 85%
See 2 more Smart Citations
“…This perhaps represents a partial compensation, in which energy is stored in phosphoanhydride bonds of inositol pyrophosphates rather than polyP. It is clear that the additional energy stored in the phosphoanhydride bonds of InsP 7 and InsP 8 in ppk1 will not be equal to that accumulated in WT polyP. However, these results do confirm a metabolic interplay between these two families of phosphate-rich molecules and their ability to regulate or be regulated by cellular energy metabolism.…”
Section: Altered Atp and Accumulation Of Inositol Pyrophosphates In Pmentioning
confidence: 85%
“…The analysis of inositol phosphates extracted from WT and ppk1 cells revealed that the ratio of InsP 7 and InsP 8 to their precursor InsP 6 is significantly altered (Fig. 5A).…”
Section: Altered Atp and Accumulation Of Inositol Pyrophosphates In Pmentioning
confidence: 99%
See 1 more Smart Citation
“…TbIP 3 R in T. brucei was demonstrated by endogenous gene tagging (13), by studies using specific antibodies (14), and by proteomic (14) and functional (13) studies. Interestingly, when TbIP 3 R (13) or the IP 3 Rs of Capsaspora owczarzaki (another protist in which biochemical characterization of the channel was done (34)) are expressed in DT40 -3KO cells (chicken lymphocytes in which the three vertebrate IP 3 R have been knocked out), the proteins localize to the ER.…”
Section: Crispr/cas9-mediated Endogenous Tagging In T Cruzimentioning
confidence: 99%
“…However, the immunofluorescence evidence reported was disputed (12), because there was no clear reticular pattern or co-localization with a T. brucei ER marker, TbBiP, in the figures published (11). In addition, the T. brucei IP 3 R localized to the acidocalcisomes as demonstrated using antibodies against the endogenous tagged protein (13) and specific antibodies against the protein (14), as well as proteomic and functional analyses (13,14). In this work, we report the acidocalcisome localization of TcIP 3 R.…”
mentioning
confidence: 99%